2021
DOI: 10.1017/s002221512100150x
|View full text |Cite
|
Sign up to set email alerts
|

The use of magnetic resonance imaging in the investigation of patients with unilateral non-pulsatile tinnitus without asymmetrical hearing loss

Abstract: Background Tinnitus is a common condition presenting to the ENT out-patient clinic. Vestibular schwannomas are benign cerebellopontine angle tumours that usually present with unilateral sensorineural hearing loss. Magnetic resonance imaging of the internal auditory meatus is the definitive investigation in their detection. The current recommendation is for unilateral tinnitus patients to undergo magnetic resonance imaging of the internal auditory meatus to exclude vestibular schwannoma. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The study characteristics can be found in Table 1. Two studies exclusively reported on patients with unilateral tinnitus with no asymmetrical hearing loss (13,17). The other five studies reviewed all MRI IAM requests for audiovestibular complaints and reported on patients presenting with unilateral tinnitus without hearing loss in their results section.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study characteristics can be found in Table 1. Two studies exclusively reported on patients with unilateral tinnitus with no asymmetrical hearing loss (13,17). The other five studies reviewed all MRI IAM requests for audiovestibular complaints and reported on patients presenting with unilateral tinnitus without hearing loss in their results section.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six of the studies recorded the audiogram results of the patients. The largest study (13) reported on 566 patients with unilateral tinnitus alone, whereas the smallest study (14) included had 23 such patients. Three of the studies did not mention the type of tinnitus of their patients and whether No it was pulsatile or not.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Összesen 566 felvétel közül 3-nál igazolódott vestibularis schwannoma, illetve 134 esetben incidentális eltérések (például vascularis encephalopathia, "üres sella" szindróma, corpus pineale cysta stb.). Az eredmények alapján a vestibularis schwannoma az egyoldali tinnitus ritka oka, kizárása azonban feltétlenül szükséges [24]. Pulzatilis tinnitusformák esetén -a carotis-vertebralis Doppler-ultrahangvizsgálathoz hasonlóan -az agykoponya-MRI jelentősége is kiemelten fontos lehet, ezekben az esetekben számos eltérést igazolhat, mint például glomus tympanicum tumor, a. carotis stenosis, a. carotis dissectio, agyalapi aneurysma, intracranialis hypertensio (pseudotumor cerebri), arteriovenosus fistula stb.…”
Section: Megbeszélésunclassified
“…Screening guidelines for vestibular schwannomas, incidence of significant pathology in nasal polyps, and impact of in-office biopsy in head and neck cancer Jonathan Fishman and Edward Fisher, Senior Editors Magnetic resonance imaging (MRI) of the internal auditory meatus (IAM) is the most common imaging requested for patients with audiovestibular symptoms to exclude a vestibular schwannoma. 1 The UK's National Institute for Health and Care Excellence (NICE) has recently produced guidelines recommending criteria for requesting MRI of the IAM (e.g. if there is an asymmetry on pure tone audiometry of 15 dB or more at any two adjacent test frequencies, using test frequencies of 0.5, 1, 2, 4 and 8 kHz; and if there are localising signs irrespective of audiogram results).…”
mentioning
confidence: 99%